Construction of one-frequency solutions of boundary-value problems for a nonautonomous wave equation - Sokil, B. I. (Ukrains’kyi Matematychnyi Zhurnal, 1994)
By using special periodic Ateb-functions, we construct asymptotic representations of one-frequency solutions of boundary-value problems for a nonautonomous wave equation.